Expression of NFIL3 and CEBPA regulated by IFNT induced-PGE2 in bovine endometrial stromal cells during the pre-implantation period - Bai, Rulan; Kusama, Kazuya; Matsuno, Yuta; Bai, Hanako; Sakurai, ﻿Toshihiro; Kimura, Koji; Imakawa, Kazuhiko (Frontiers in Endocrinology, 2023)
Prostaglandin E2 (PGE2) is considered as a luteoprotective factor, influencing the corpus luteum during the early pregnant period in the bovine species. Cyclic AMP (cAMP) is activated in response to PGE2 and plays a role in many physiological processes. The maternal recognition signal, interferon τ (IFNT), induces PGE2 secretion from the endometrial epithelial cells, the function of which in stroma cells has not been completely understood. In this study, PGE2 was found to activate cAMP in the bovine endometrial stromal cells (STRs). STRs were then treated with forskolin to activate the cAMP signaling, from which RNA extracted was subjected to global expression analysis. Transcripts related to transcription regulatory region nucleic acid binding of molecular function, nucleus of cellular component, and mitotic spindle organization of biological processes were up-regulated in cAMP-activated bovine STRs. An increase in the transcription factors, NFIL3, CEBPA, and HIF1A via the cAMP/PKA/CREB signaling pathway in the bovine STRs was also found by qPCR. Knockdown of NFIL3, CEBPA, or HIF1A blocked forskolin-induced PTGS1/2 and IGFBP1/3 expression. Moreover, NFIL3 and CEBPA were localized in endometrial stroma on pregnant day 17 (day 0 = estrous cycle), but not on cyclic day 17. These observations indicated that uterine PGE2 induced by conceptus IFNT is involved in the early pregnancy-related gene expression in endometrial stromal cells, which could facilitate pregnancy establishment in the bovine.